Effect of Growth Rate on Physical and Mechanical Properties of 4-year-old Acacia mangium Wood from Wonogiri, Central Java - Fanny Hidayati; Ramadhani Ayu Purnama; Harry Praptoyo; Sri Sunarti (Jurnal Ilmu Kehutanan)
Increasing solid wood demand provides an opportunity to fast-growing wood species such as Acacia mangium as semi construction and construction materials. In general, the quality of wood is affected by growth characteristics such as radial growth rate. The study about effect of growth rate on the properties of mangium wood is limited in Indonesia. Therefore, this study aimed to determine the physical and mechanical properties of mangium wood at different growth rates. Furthermore, relationship between basic density and other properties was clarified. The nine mangium trees of 4-year-old used in this study were planted in Wonogiri Regency, Central Java. Basic density, shrinkage, T/R ratio, static bending strength (MOE and MOR), compressive strength parallel and perpendicular to grain were determined. The results were analyzed with one-way ANOVA. As a result, the physical and mechanical properties of the woods showed no significant difference in three different categories of growth rates, except for radial shrinkage. Furthermore, the basic density is positively significant correlated with radial and tangential shrinkage and also compressive strength parallel and perpendicular to grain. Based on these results, it is suggesting that basic density is a good indicator for predicting physical and mechanical properties of mangium wood.